Pengaruh waktu milling terhadap ukuran butir forsterite (Mg2SiO4) dari batuan dunit di daerah Jorong Tongar Nagari Aur Kuning, Kabupaten Pasaman Barat - Vera Firmansari (Department of Physics – Universitas Negeri Padang UNP, 2016)
Dunit made with material engineering techniques will bring up a new phase is forsterite. Forsterite has economic value. Forsterite in the formed nanoparticle size can be used as a coating material in the iron and steel melting place because the size of the nano has properties very strong, hard, and resistant to corrosion. The purpose of this study was to investigate the influence of milling time on grain size forsterite of rock dunit. Type of research is experiment. Method of research is forsterite synthesized by mechanical activation using the High Energy Milling 3D Ellipse to obtain nano grain size of forsterite. The results of the milling characterized using X-Ray Diffraction and Scanning Electron Microscope. The results of this study show the crystal structure that is formed during the milling time 5 hours, 10 hours, 20 hours, 40 hours is orthorhombic. Result of Scanning Electron Microscope the grain size of nanoparticle forsterite for variation milling 5 hours, 10 hours, 20 hours, and 40 hours are 630 nm, 717 nm, 454 nm dan 354 nm